Relationship Between Social Identity of Football Supporters and Conflicts (Study of The Jakmania Depok City) - Kaligis, Retor AW (Universitas Negeri Semarang, 2020)
This study examined the relationship of The Jakmania's social identity with the conflict of supporters. The Jakmania members who come from various ethnic and regions sought identity as